2002
DOI: 10.1080/15287390252800882
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lipid Peroxidation and Changes of Trace Metals in Rats Following Chronic Manganese Chloride Exposure

Abstract: The aim of this study was to investigate the effects of chronic, daily, 30-d administration of manganese chloride (MnCl2) to male Sprague-Dawley rats on lipid peroxidation and changes of trace elements (manganese, iron, copper, zinc) in various brain regions. Rats were intraperitoneally injected with MnCl2 (20 mg/kg) once daily for 30 consecutive days. The Mn accumulated in frontal cortex, corpus callosum, hippocampus, striatum, hypothalamus, medulla, cerebellum, and spinal cord. Malondialdehyde, an end produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…PC12 cells treated for 48 h also presented a reduced content of Chol and of eicosapentaenoic acid (C20:5) and docosahexaenoic acid (C22:6), which are n-3 PUFA involved in important membrane-mediated processes [40]. The decrease in n-3 PUFA could be due to an increase in lipid peroxidation, since it has been reported that Mn-induced apoptosis is associated with oxidative stress [41][42][43]. Interestingly, the overall modifications of the lipid content results in an increase of phospholipids/ Chol and in a decrease of PE/PC ratios, which indicated an increase in membrane fluidity.…”
Section: Discussionmentioning
confidence: 95%
“…PC12 cells treated for 48 h also presented a reduced content of Chol and of eicosapentaenoic acid (C20:5) and docosahexaenoic acid (C22:6), which are n-3 PUFA involved in important membrane-mediated processes [40]. The decrease in n-3 PUFA could be due to an increase in lipid peroxidation, since it has been reported that Mn-induced apoptosis is associated with oxidative stress [41][42][43]. Interestingly, the overall modifications of the lipid content results in an increase of phospholipids/ Chol and in a decrease of PE/PC ratios, which indicated an increase in membrane fluidity.…”
Section: Discussionmentioning
confidence: 95%
“…An elevated level of MDA reflects, to a certain degree, tissue injury resulting from oxidative damage. Results from animal studies showed an alteration of MDA level in animals exposed to Mn (Chen et al, 2002). Misiewicz and colleagues (1999) also demonstrated an increased serum concentration of MDA in workers engaged in the production of Fe-Mn alloys.…”
Section: Biomarkers Of Mn Toxicitiesmentioning
confidence: 99%
“…Some researchers have reported an alteration of MDA level in animals exposed to manganese. 26 Misiewicz and his colleagues 27 also demonstrate an increased serum concentration of MDA in workers engaged in the production of ironmanganese alloys. Therefore, the levels of either SOD or MDA, or both, in the systemic circulation may serve as the useful biomarker(s) for oxidative status after long-term, lowlevel exposure to the welding fume among career welders.…”
mentioning
confidence: 97%
“…Because in vivo exposure to manganese has been shown to induce the oxidative stress, 26,27 the activities of SOD and levels of MDA were assayed to test the hypothesis that altered SOD and/or MDA among welders may be used as the biomarker(s) for manganese exposure in humans. Table 4 summarizes the comparisons made between welders and control subjects.…”
Section: Systemic Status Of Oxidative Stressmentioning
confidence: 99%